Biological Activity of Recombinant Accessory Cholerae Enterotoxin (Ace) on Rabbit Ileal Loops and Antibacterial Assay - Shaghayegh Anvari; Shahin Najar Peerayeh; Mehrdad Behmanesh; Mina Boustanshenas (Cell Journal, 2012)
Objective: Vibrio cholerae (V. cholerae) causes a potentially lethal disease named cholera. The cholera enterotoxin (CT) is a major virulence factor of V. cholerae. In addition to CT, V. cholerae produces other putative toxins, such as the zonula occludens toxin (Zot) and accessory cholera enterotoxin (Ace). The ace gene is the third gene of the V. cholerae virulence cassette. The Ace toxin alters ion transport, causes fluid accumulation in ligated rabbit ileal loops, and is a cause of mild diarrhea. The aim of this study is the cloning and overexpression of the ace gene into Escherichia coli (E. coli) and determination of some characteristics of the recombinant Ace protein.Materials and Methods: In this experimental study, the ace gene was amplified from V. cholerae strain 62013, then cloned in a pET28a expression vector and transformed into an E. coli (DH5 α) host strain. Subsequently, the recombinant vector was retransformed into E. coli BL21 for expression, induced by isopropythio-β-D-galctoside (IPTG) at a different concentration, and examined by SDS-PAGE and Western blot. A rabbit ileal loop experiment was conducted. Antibacterial activity of the Ace protein was assessed for E. coli, Stapylococcus aureus (S. aureus), and Pseudomonas aeruginosa (P. aeruginosa).Results: The recombinant Ace protein with a molecular weight of 18 kDa (dimeric form) was expressed in E. coli BL21. The Ace protein showed poor staining with Coomassie blue stain, but stained efficiently with silver stain. Western blot analysis showed that the recombinant Ace protein reacted with rabbit anti-V. cholerae polyclonal antibody. The Ace protein had antibacterial activity at a concentration of ≥200 μg/ml and caused significant fluid accumulation in the ligated rabbit ileal loop test.Conclusion: This study described an E. coli cloning and expression system (E. coli BL21- pET-28a-ace) for the Ace protein of V. cholerae. We confirmed the antibacterial properties and enterotoxin activity of the resultant recombinant Ace protein.